Optimization of Unit IV Intelligence Raising to Prevent the Spread of Ormas’ Radicalism in the Jurisdiction of Sukoharjo Police - Womsiwor, Varrel Avanda (Police Studies Review, 2024)
The background of this research is that there is still the spread of radicalism by mass organizations in the jurisdiction of the Sukoharjo Police. The Sukoharjo District Police took precautions to overcome the spread of mass organization radicalism through intelligence-raising activities by the Intelligence and Security Unit. This study uses a qualitative approach, with a descriptive analysis type of research, as well as data collection techniques through interviews, observation and document studies. This study uses the SWOT theory, Management and Its Elements and uses the concepts of Intelligence Raising, Radicalism and MOTL. The results of the study show that intelligence-raising activities by unit IV satintelkam are not optimal, this is caused by constraints that occur both from internal factors, developments in science and technology which make the spread of radical ideas can be carried out quickly through social media and plans for many fundraising activities with different targets. various because there are many mass organizations, NGOs and exconvicts assisted by ex-convicts who must be continuously monitored. The ideal conditions that researchers hope for are good management from the initial planning stage to the implementation of activities to the report on the results of task implementation in the form of products and the existence of support that can make fundraising optimalization activities by unit IV. Problem solving steps taken to achieve the ideal conditions expected, include involving stakeholders and side agencies with coordination and collaboration with the hope that support related to fundraising activities will continue to exist with the limitations of Satintelkam, Rearrange budgets and activities that become priority, expanding intelligence networks that are both open and closed and updating links with supporting facilities and infrastructure that can support the implementation of tasks in the field.